Using Electronic Data Interchange (EDI) to Improve the Efficiency of Accounting Transactions - Anderson, Shannon W.; Lanen, William N. (The Accounting Review, 2002)
Electronic data interchange (EDI) is an information technology that standardizes the exchange of information between transacting parties. Using data from a major U.S. office furniture manufacturer that adopted EDI primarily to improve the efficiency of accounting transactions, we evaluate whether EDI reduces order-processing time (the time from sales order receipt to sales order scheduling) and whether this improvement is greater for more complex orders. Our measure of complexity reflects both the mix of different products the dealer orders as well as features and options the dealer selects for each product in the order. We find that EDI is associated with faster order processing, independent of complexity, and that EDI mitigates most of the negative effects of complexity on processing time. We also find that dealers learn to submit error-free orders to the manufacturer, and that previous errors provide feedback that helps dealers submit more accurate orders. However, we find only mixed evidence that order complexity impedes learning.